Philo's scriptures : citations from the Prophets and Writings : evidence for a Haftarah cycle in Second Temple Judaism - Cohen, Naomi G. (Supplements to the Journal for the Study of Judaism, 2007)
It is indeed remarkable that although Philo has quoted extensively from the Pentateuch, his works contain no more than forty-six references to the Prophets and Writings. The author provides a convincing explanation for every one of these citations. It corroborates the thesis that Philo availed himself of lexicographic aids and midrashic material, and further, that even when the language of their composition was Hebrew/Aramaic, that he used them in Greek translation. It identifies a circle engaged in esoteric philosophic allegorization of Scriptures, with which Philo associated, and it finds that the specific quotations from the Prophets point to the existence, already in the 1st century CE, of a traditional Haftarah Cycle . The book fills a long felt lacuna.